THE HUNT FOR SELF: WALDEINSAMKEIT AND DOPPELGÄNGER IN RICHARD CONNELL'S "THE MOST DANGEROUS GAME" - Jafari Langroudi, Narjess (Armenian Folia Anglistika, 2025)
This paper excavates the philosophical dimensions inherent in Richard Connell's The Most Dangerous Game, underscoring how they affect the story's deeper layers of meaning. Rainsford's initial indifference as the hunter is tested when he is thrust into the role of the hunted. This experience compels him to face the moral intricacies of existence. Central to his journey is the concept of Waldeinsamkeit – the solitary excursion found in the forest. The wilderness, a space evocative of primal instincts and survival, becomes the setting for Rainsford's personal transformation. His encounter with General Zaroff is not only a physical tribulation but also a symbolic confrontation with his darker self, or doppelgänger, revealing the opaque and unpredictable aspects of human nature. The story questions whether Rainsford’s transformation ultimately leads to a more humanized perspective or further alienates him from his humanity, leaving this question unresolved.
Keywords: Waldeinsamkeit; Doppelgänger; Dehumanization; Indeterminacy; Tribulation